PATTERNS OF ENT- HEAD AND NECK SURGERIES IN A TERTIARY HOSPITAL OF NEPAL - Maharjan, Alisha; Dhungana, Sundar; Acharya, Aakash (Journal of Chitwan Medical College, 2024)
Background: Otorhinolaryngology, also known as Ear, Nose, Throat, Head, and Neck Surgery (ENT-HNS), deals with a variety of illnesses. Scientific progress has significantly changed this field worldwide. Despite this, Nepal, as a developing nation, lacks data on ENT surgeries. Our study seeks to analyse surgery trends to improve planning and treatment at the policy-making level. Methods: This descriptive cross-sectional study was conducted at the Nepal APF Hospital’s Department of ENT-HNS. The study collected data from patients of both sexes and all ages who had operations performed by the ENT department between January 2022 and December 2023. Data were analyzed, and the findings were published to search for patterns in the various surgical procedures. Results: Of the 370 surgeries performed during these two years, major surgeries included tympanoplasty, septoplasty, adenotonsillectomy, endoscopic sinus surgery, and thyroid surgery. Common intermediate and minor surgeries included excision of minor and benign head and neck lesions, cervical lymph nodes, and tongue biopsy. Both individual types and overall surgeries were more frequent in the second year compared to the first. Conclusions: In our research, the trend of conducting significant otolaryngology and head and neck surgeries at our institution is on the rise. The increasing volume underscores the necessity for departmental expansion, incorporation of recent advancements, establishment of super-specialties, and specialized training of surgeons, particularly in government hospitals like ours.